Diseño e implementación de un sistema interactivo mediante tecnología Kinect v2.0 para desarrollar las habilidades psicomotrices en personas con discapacidad visual. - Cujano Ortega, Mayra Viviana (2016)
The research project "DESIGN AND IMPLEMENTATION OF AN INTERACTIVE SYSTEM USING TECHNOLOGY KINECT V2.0 TO DEVELOP PSYCHOMOTOR SKILLS VISUALLY IMPAIRED PEOPLE", It is developed in order to be a contribution for people who have a visual impairment. The interactive system is comprised of hardware elements that is a computer Toshiba Core I5, 6GB of RAM and a Kinect version 2.0 sensor with its own adapter for Windows. It also has software elements such as Kinect SDK, Visual Studio 2013 and packages needed for voice recognition and audio, which when coupled allow the system to interact without using any control device. The name given to this interactive system is KinectMove which has five activities to develop psychomotor skills, the same that have been programmed in C # compiler of Visual Studio, the user through voice commands initialize the recording application data such as name, age, sex, allowing you to select the activity you want to perform. Move Kinect also has a remote data record are hosted on a web server, allowing any user to view the report generated by the application. The storage of these data makes using the SQL Server 2008 software because it enables work in client-server mode. In conclusion Move Kinect can recognize the skeleton of the user in any environment you want to perform the activities and interact with it through voice commands and audio, for future work is recommended using filters which capture only the user's voice, as the Kinect is not a smart sensor and tends to confuse the data it receives.